so I have an equation:
ln (2x+1) + ln(x-2) -2lnx = 0
so to be able to use product rule I added the 2lnx and cancelled out for equality rule
ln(2x+1)+ln(x-2) = 2 ln x
then ln((2x+1)(x-2)) = 2 ln x, can cancel out the ln so we have
(2x+1)(x-2) = 2x.
Im little confused on what to do next. Should I foil out the left side then add the right? Think im forgetting a step here to fully solve this. Thanks
actually had a slight typo in the problem. But here we go
going off what you had this is what we actually see (x-3 not x-2)
(2x+1)(x-3) = x^2..can we divide out the x's?
[(2x+1)(x-2)]/x^2 = [(2+1)(-3)]/x = 0
(2+1)(-3) = x
everything I know tells me this should be wrong..since x^2 usually means we should have two answers.
However I was unsure on how to factor it..
yes I see, so we get
2x^2-6x+x-3 = x^2
2x^2-5x-3 = x^2
2x^2-x^2-5x-3 = x^2-5x-3 = 0
this doesn't factor even so x= +- (5+sqrt(37))/2
trying to relearn this on your own is rather difficult lol :/